Editorial: Guinea Worm: the final push to eradication in South Sudan - Edward Kenyi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
The world is getting closer to eradicating Guinea worm, which will join the only other disease to be eradicated in the world - small pox. Although South Sudan cannot sleep on its laurels for now as it enters the pre-certification phase, the news that it has interrupted the transmission is one that must be applauded. Thanks to the relentless work of the hundreds of health workers on the ground, and the support of the global community.